Management and outcomes of patients admitted with type 2 myocardial infarction with and without standard modifiable risk factors - Sokhal, Balamrit Singh; Matetić, Andrija; Paul, Timir K; Velagapudi, Poonam; Lambrinou, Ekaterini; Figtree, Gemma A; Rashid, Muhammad; Moledina, Saadiq; Vassiliou, Vassilios S; Mallen, Christian; Mamas, Mamas A. (My University, 2023)
Whilst it is known patients without standard modifiable cardiovascular risk factors (SMuRF; hypertension, diabetes, hypercholesterolaemia, smoking) have worse outcomes in Type 1 acute myocardial infarction (AMI), the relationship between type 2 AMI (T2AMI) and outcomes in patients with and without SMuRF is unknown. This study aimed to determine the prevalence, characteristics and clinical outcomes of patients hospitalised with T2AMI based on the presence of SMuRF.
Keywords: Acute myocardial infarction; National Inpatient Sample; Outcomes; Risk factors